2019
DOI: 10.1097/corr.0000000000000710
|View full text |Cite
|
Sign up to set email alerts
|

Are Hooded, Crosslinked Polyethylene Liners Associated with a Reduced Risk of Revision After THA?

Abstract: Background Hooded acetabular liners and head sizes $ 32 mm have both shown to have a beneficial effect on the revision rate for dislocation in THA. Experience with noncrosslinked polyethylene (nonXLPE) raised concerns regarding the risk of impingement damage, loosening, and osteolysis with hooded liners; however, the evidence for this in crosslinked polyethylene (XLPE) is inconclusive. The interaction between different femoral head sizes and hooded liners is not well understood, and it is unclear whether hoode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…One case (1.3%) of osteolysis was confirmed in the standard group, whereas no osteolysis was observed in the elevated-rim group. Similarly, a recent analysis based on the Australian registry [35] found that XLPE lipped liners were not associated with an increased revision rate for aseptic loosening at a mean of 5 years. Revisions for breakage of the acetabular liner were extremely rare, with 11 for lipped liners (0.009%) and four for standard liners (0.006%).…”
Section: Elevated-rim and Offset Linersmentioning
confidence: 88%
“…One case (1.3%) of osteolysis was confirmed in the standard group, whereas no osteolysis was observed in the elevated-rim group. Similarly, a recent analysis based on the Australian registry [35] found that XLPE lipped liners were not associated with an increased revision rate for aseptic loosening at a mean of 5 years. Revisions for breakage of the acetabular liner were extremely rare, with 11 for lipped liners (0.009%) and four for standard liners (0.006%).…”
Section: Elevated-rim and Offset Linersmentioning
confidence: 88%
“…However, findings like these that are hard to explain-and require so much speculation to arrive at an explanation-should also be viewed with some suspicion, as they suggest that unmeasured confounding variables might also be at work here. For that reason, even the primary study findings in the study by Bauze and colleagues [1] really should be independently confirmed if we are to have confidence in it.…”
mentioning
confidence: 90%
“…Although Bauze and colleagues [1] found that hooded liners were associated with reduced revision risks, we still need to determine whether this result is implant-specific or generalizable to all hooded designs. The study included all uncemented cup designs but did not consider whether the analyzed cups were available in both hooded and nonhooded versions.…”
mentioning
confidence: 96%
See 2 more Smart Citations